Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1475-6803.1990.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Changes and Common Stock Returns of Financial Institutions: Revisited

Abstract: In this paper the interest rate sensitivity of common stock returns of financial firms is re‐examined. Considered here are (1) current, anticipated, and unanticipated changes in interest rates; (2) depository and nondepository firms; and (3) three different‐maturity interest rate indices. Results lend strong support for a negative effect of both current and unanticipated interest rate changes. Although some exceptions are observed, stock returns of most subsectors of both financial and nonfinancial firms are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0
6

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 11 publications
10
85
0
6
Order By: Relevance
“…Both Bae (1990) and Dinenis and Staikouras (1998) also found a significant inverse relationship between interest rates and stock returns; furthermore both studies showed the sensitivity of returns is an increasing function of the interest rate measure employed. Flannery and James (1984) found evidence that the sensitivity of stock price changes and interest rates is highly related to the duration of the firm's assets and liabilities 2 .…”
Section: Asset Pricingmentioning
confidence: 85%
“…Both Bae (1990) and Dinenis and Staikouras (1998) also found a significant inverse relationship between interest rates and stock returns; furthermore both studies showed the sensitivity of returns is an increasing function of the interest rate measure employed. Flannery and James (1984) found evidence that the sensitivity of stock price changes and interest rates is highly related to the duration of the firm's assets and liabilities 2 .…”
Section: Asset Pricingmentioning
confidence: 85%
“…Faiz oranları ve BİST100 hisse senedi fiyatları arasında ise beklenildiği gibi literatürle uyumlu olarak ( Pearce & Roley ,1985;Hardouvelis, 1987;Flannery & James , 1984;Cook & Hahn , 1988;Bae, 1990;Fung vd., 1990;Gjerde & Saettem , 1999;Aras & Müslümov , 2003;Alam & Uddin , 2009;Vejzagic & Zarafat ;2013) çalışmalarında olduğu gibi negatif ilişki tespit edilmiştir.…”
Section: Uzun Dönem Eş-bütünleşme Katsayılarının Tahminiunclassified
“…Artan faiz oranları firma maliyetlerini etkileyecek maliyetler ise karlılığı etkileyecektir. Bu bağlamda artan faiz oranları karlılığı azaltacağından hisse senedi getirilerini azaltacak, diğer yandan yeni hisse senetlerinin alımını azaltacak ve hisse senedi fiyatının düşmesine neden olacaktır (Pearce & Roley, 1985;Bae, 1990;Husain, Zaman & Baloch, 2014;Toraman & Başarır, 2014 Döviz kuru ve hisse senedi ilişkisi konusunda; Qiao (1997), Bhattacharya & Mukharjee (2002), Fang & Miller (2002), Hatemi & Irandoust (2002), Nath & Samanta (2003), Misra (2004), Phylaktis & Ravazollo (2005), Tabak (2006), Ayaz (2006), Aydemir & Demirhan (2009), Kutty (2010), Kapusuzoğlu & İbicioğlu (2010), Zia & Rahman (2011), Savaş & Can (2011, Berke (2012), Ray (2012), Paramati & Gupta (2013), Büberkökü (2013), Şentürk & Dücan (2014), Ceylan & Şahin (2015), Kendirli & Çankaya (2015), Öncü, Çömlekçi, Yazgan & Bar (2015), Coşkun & Ümit (2016), Belen & Karamelikli (2016) gibi araştırmacılar, hisse senedi ve faiz oranları arasındaki ilişki konusunda ise Pearce & Roley (1985), Hardouvelis (1987), Flannery & James (1984), Cook & Hahn (1988), Bae (1990), Fung, Lie & Moreno (1990, Gjerde & Saettem (1999), Aras & Müslümov (2003), Davig & Gerlach (2006), Alam & Uddin (2009…”
Section: Introductionunclassified
“…Another set of studies propose that innovations in interest rate variable would have higher explanatory power for returns as compared to expected interest rates. Bae (1990) studied the impact of expected interest rates and surprises to such expectations for stock returns of depository and non depository institutions. The empirical analysis included three interest rate indices of different maturities and results reported a higher sensitivity for surprises to yield curve with longer maturity.…”
Section: Literature Reviewmentioning
confidence: 99%